Design for Sustainability: Countering the Drivers of Unsustainability in Development Projects - Meyer, Isabel; Marais, Mario Alphonso (The Journal of Community Informatics)
Development projects aim to make a difference in communities. Funders often require that the intervention needs to last, or that it needs to effect change that will last, over an extended period of time. In sho rt, a sustainable difference needs to be made and this is an important measure of success.  However, there are inherent drivers in the combi ned system of donors and beneficiaries that counter sustainability. Th is article explores these drivers, and identifies project design eleme nts that need to be in place in order to promote sustainability by cou ntering the drivers. This approach is applied to an education project, and implications for ICT4D projects are developed.
Keywords: Development; Project design; Systems Approaches; sustainability